THE EFFECT OF TELEVISION PROGRAM ON CHILDREN'S FOREIGN LANGUAGE ACQUISITION - Rajulain, Muhammad (Fakultas Bahasa, Seni, dan Budaya, Universitas Negeri Yogyakarta, 2019)
(Title: The Effect of Television Program on Children's Foreign Language Acquisition). Since it was first discovered in the 1920s, television has become an integral part of modern human life. The influence of television programs or programs on children's foreign language acquisition has become an interesting research subject to study. This study aims to determine the effect of television programs on the acquisition of foreign languages in a subject aged two years and three months using a qualitative method where the researcher also acts as an observer. The data obtained is recorded in the form of a diary, and interviews are conducted with parents and the people closest to the subject to obtain accurate data. The results of the study showed that the television programs being watched did not have a significant effect on the acquisition of foreign languages on the subjects studied. Keywords: Television programs, foreign language acquisition, children